Diurnal fluid expression and activity of intervertebral disc cells. - Sivan, S; Neidlinger-Wilke, C; Würtz, K; Maroudas, A; Urban, J (2006)
The intervertebral discs are large cartilaginous structures situated between the vertebral bodies, occupying around one third of the length of the spinal column. They act as the joints of the spine and carry mechanical load arising from body weight and muscle activity. Loads change with every alteration of posture and activity and the discs thus undergo a diurnal loading pattern with high loads on the discs during the day's activity and low loads on it at night during rest. As the disc is an osmotic system, around 25% of the disc's fluid is expressed and re-imbibed during each diurnal cycle with consequent changes in the osmotic environment of the disc cells. Here, present information on the effect of osmotic changes in disc cell metabolism is reviewed; results indicate that prevailing osmolarity is a powerful regulator of disc cell activity.